2020
DOI: 10.1200/jco.2020.38.15_suppl.5554
|View full text |Cite
|
Sign up to set email alerts
|

Cabazitaxel versus enzalutamide/abiraterone in CARD eligible mCRPC patients with or without germline HRR defects.

Abstract: 5554 Background: The CARD trial proved that in mCPRC patients (pts), previously treated with docetaxel and an androgen-receptor signaling inhibitor (ARSi), cabazitaxel (CBZ) significantly improves progression-free (PFS) and Overall Survival (OS) compared with the alternative ARSi. Concurrently, the PROFOUND study showed the superiority of olaparib vs. ARSi in pts with similar prior treatment history and genetic alterations in Homologus Recombination DNA repair related genes (HRR). Methods: PROREPAIR-B (NCT030… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A post hoc analysis of the PROREPAIR-B study showed that the outcomes of patients with germline HHR mutations were worse than those of noncarriers following treatment with cabazitaxel [30]. Aldea et al [31] analysed the response to cabazitaxel in mCRPC patients with germline or somatic DDR defects and found no difference in response rates in patients with and without such alterations.…”
Section: Key Pointsmentioning
confidence: 99%
“…A post hoc analysis of the PROREPAIR-B study showed that the outcomes of patients with germline HHR mutations were worse than those of noncarriers following treatment with cabazitaxel [30]. Aldea et al [31] analysed the response to cabazitaxel in mCRPC patients with germline or somatic DDR defects and found no difference in response rates in patients with and without such alterations.…”
Section: Key Pointsmentioning
confidence: 99%